Preclerkship Point-of-Care Ultrasound: Image Acquisition and Clinical Transferability. (July 2020) - Khoury, Michel; Fotsing, Salomon; Jalali, Alireza; Chagnon, Nicolas; Malherbe, Stéphanie; Youssef, Nermine
Introduction: The integration of point-of-care ultrasound (POCUS) in preclerkship medical education is currently popular and based on the notion that POCUS may improve diagnostic and procedural skills in medical students. However, empirical evidence demonstrating that POCUS can enhance clinical skills in preclerkship students has been lacking. We sought to evaluate anatomical sonographic knowledge and ultrasound generation capabilities associated with the implementation of a 3-h echocardiography training camp led by 2 emergency physicians and using a flipped classroom design. Methods: Preclerkship students from the University of Ottawa (n = 32) were recruited to participate. A flipped classroom model was adopted, providing students with a 3-chaptered peer-designed, expert validated ultrasound manual before the workshop, to maximize scanning times (2 h of reading). A pretest Likert-type design was used to assess student perception of the ultrasound tool. Similarly, a pretest/post-test model was used to assess sonographic anatomical identification. In addition, a subsequent Objective Structured Clinical Examination (OSCE) test was done 3 weeks after the hands-on session, to evaluate image generation (4 cardiac views: parasternal long, parasternal short, subxiphoid, and apical 4 chambers), understanding of knobology and structural labeling. Results: For the sonographic anatomy, there was a statistically significant increase ( P < .001) between pretest (average = 12.12) and post-test (average = 18.85). The OSCE, which also ascertained knowledge retention, found that 81% of students were able to generate all 4 cardiac views perfectly, 6% were able to obtain 3 views, 10% obtained 2 views and 3% successfully generated a single view. The most challenging scan to generate was the apical 4-chamber view. Conclusion: The positive outcomes stemming from this study reinforces the notion that formal curricular integration of POCUS at the preclerkship level has tangible benefits for medical students.